DIVISION OF COMPETENCES BETWEEN THE EUROPEAN UNION AND THE MEMBER STATE (EU and comparative law issues and challenges series (ECLIC), 2019)
Starting from the very name of the Scientific Conference “The European Union and the Member States - Legal and Economic Issues”, the authors consider that the legislative division of competences between the European Union and the Member States is a key issue for their actions and their mutual relations. Therefore, the aim of the work is to establish a vertical distribution of powers in the European Union and to analyse comparatively the constitutional division of competences between different territorial levels of government in selected European states with federal regulation. The vertical division of competences within the Union is a question of constitutional importance as one of the principles of the structure of authority within its territory. The importance of a vertical division of competences is reflected in particular in the fact that it involves the adoption of very complex decisions on whether a matter should be regulated at a central (European) or at national (state) level. It is important to point out that the process of transferring competence from the higher level (European Union) to the lower forms of territorial organization (Member States) presupposes the instrument and the premise of democratization. At the same time, the range of competences is a form of limitation of the powers of the European Union, within the limits of the competences assigned to it by a primary act. The division of the jurisdiction, apart from legal regulation, has an economic effect. The better the division is, the more effective are the Union and the member states in providing faster and better public services to citizens, without spending much of the state resources, leading to better balance and the prevention of abuse of power. Work is divided into several interrelated chapters. After the introduction, it is primarily concerned with clarifying general questions about the vertical division of competences between different territorial levels of government. Within this chapter, it starts from the consideration of conceptual definitions, through the analysis of the way of determining competence between territorial levels of authority, the competence to allocate affairs between territorial levels of authority to the vertical division of jurisdiction as a constraint of power. The central part of the paper deals with the analysis of the delimitation of competences between the European Union and the Member States as defined in the Lisbon Treaty, which includes: a) exclusive competence of the European Union, b) shared competences between the European Union and the Member States and c) competence to support, coordinate and complement Member States’ actions. Particular emphasis is placed on the following principles: the conferred powers and subsidiarity and proportionality. They are based on the implementation of competences between the Union and the Member States. These principles represent the basic principles for the functioning of the European Union and the creation of its law. Within this framework, the exclusive competence of the Member States, the functioning of the Union outside its established jurisdictions, the principle of genuine co-operation between the European Union and the Member States, as well as the obligation to apply European Union legislation adopted in the area of jurisdiction are considered. Particularly, it deals with the issue of control of the principles of authority, subsidiarity and proportionality before the Court of Justice of the European Union. The method of comparative analysis analyses the constitutionally defined vertical division of competences in the selected European federal states: the Federal Republic of Germany and Switzerland. On the basis of a comparative method, it is possible to conclude that there are similarities between vertical delimitation within the European Union and vertical distribution of jurisdiction in federal states. In addition to comparative method, regarding research methodology, the paper uses secondary research and normative and historical method.